Pathologic response after neoadjuvant chemoradiotherapy in Sudanese patients with locally advanced rectal adenocarcinoma - Abdalla, Ahmed; Alawad, Awad; Abdalla M. Ali, Hussein (International Journal of Medicine, 2015)
Background: Locally advanced rectal cancer can be down staged by neoadjuvant therapy and the resultant tumor response can be quantified histologically.Objective: This study aimed to assess pathologic response of neoadjuvant chemoradiation in patients with locally advanced rectal cancers treated in Wad Medani Teaching Hospital (WMTH) and National Cancer Institute (NCI), Wad Medani, Sudan.Patients and Methods: A total of 36 consecutive patients with locally advanced rectal cancer that were managed in WMTH and NCI during the period from 2006-2011 were reviewed. Preoperative pelvic radiotherapy was delivered.Â  The total of 46 Grays were delivered concurrently with 5- fluorouracil (5-FU) on the first and last week of radiation. Total mesorectal excision of the rectal tumour either by anterior or abdominoperineal resections was planned at 6-8 weeks from completion of preoperative treatment. The pathological response to therapy was assessed by histopathology examination of the surgical specimen.Results: Initial clinical staging of patients revealed 58.3% of them were stage T3/T4N2M0 and 41.7% were stage T3N0M0. Down-staging to stage T1/T2N0M0 was found in 36.1% and stages T3N0M0 in 30.6%. No response was seen in 8.3% of cases with stage T3/T4N2M0 while a complete clinical response (no residual) was seen in 25.0%. Complete histological response was observed 13.8%. Positive lymph-nodes metastasis was confirmed in 8.3% of cases.Conclusion: Neoadjuvant chemoradiation is a reasonable option for cases of rectal cancer and deserves further evaluation.